2013
DOI: 10.1186/1741-7015-11-187
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium, vitamin D status and mortality: results from US National Health and Nutrition Examination Survey (NHANES) 2001 to 2006 and NHANES III

Abstract: BackgroundMagnesium plays an essential role in the synthesis and metabolism of vitamin D and magnesium supplementation substantially reversed the resistance to vitamin D treatment in patients with magnesium-dependent vitamin-D-resistant rickets. We hypothesized that dietary magnesium alone, particularly its interaction with vitamin D intake, contributes to serum 25-hydroxyvitamin D (25(OH)D) levels, and the associations between serum 25(OH)D and risk of mortality may be modified by magnesium intake level.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 35 publications
3
130
0
1
Order By: Relevance
“…Studies by Rude et al [171] and Fuss et al [172] showed that high doses of vitamin D alone failed to cause improvement in serum levels of both 25(OH)D and 1,25(OH) 2 D in vitamin D deficiency states until magnesium and vitamin D were co-administered. Administration of high doses of magnesium modified the inverse association of serum 25(OH)D and CVD mortality, according to Rosanoff et al [173], who cited Deng et al [174]. Earlier studies showed that calcium intake affects magnesium retention, and vice versa [175], and that hypomagnesemia is often present with hypocalcemia [171].…”
Section: Micronutrient Combination/interaction and Effect On Cvdmentioning
confidence: 99%
“…Studies by Rude et al [171] and Fuss et al [172] showed that high doses of vitamin D alone failed to cause improvement in serum levels of both 25(OH)D and 1,25(OH) 2 D in vitamin D deficiency states until magnesium and vitamin D were co-administered. Administration of high doses of magnesium modified the inverse association of serum 25(OH)D and CVD mortality, according to Rosanoff et al [173], who cited Deng et al [174]. Earlier studies showed that calcium intake affects magnesium retention, and vice versa [175], and that hypomagnesemia is often present with hypocalcemia [171].…”
Section: Micronutrient Combination/interaction and Effect On Cvdmentioning
confidence: 99%
“…1) [11,12,14,21,[36][37][38][39][40]. These studies were published between 2005 and 2014 and comprised 449,748 individuals and 10,313 CVD deaths (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the misclassification would most likely lead to an underestimated association. Third, influence of other nutrients or dietary components such as potassium [39], calcium [12] and vitamin D [37] that are correlated with dietary magnesium could not be excluded; other nutrients may have been responsible for the observed association partly or in whole. Finally, although weighted meta-regression takes account of both within-study variances and the residual between-study heterogeneity (that is, heterogeneity not explained by the covariates in the regression) by adding random effects in the model, it is not reasonable to assume that all of the heterogeneity is explained [32,51].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…When usual Mg consumption patterns were analyzed, most population groups consumed less than the RDA. Data from the National Health and Nutrition Examination Survey (NHANES) indicate that in the US 48% of adult males and 46% of adult females do not meet the current dietary recommendation for Mg [12]. However, in Germany Mg is the most supplemented mineral with 59.4%, followed by calcium with 37.0% [13].…”
Section: Introductionmentioning
confidence: 99%